Teacher-tool relationship of Maldivian ESL teachers: A multiple case study / Aishath Wadheefa - Aishath , Wadheefa (2020)
Previous research has revealed the various ways teachers use the curriculum in classroom teaching. The way teachers use the curriculum not only impacts the effective implementation of the curriculum but, it also impacts the classroom instruction. This study intended to describe the teacher-tool relationship and the factors which shape this teacher-tool relationship. It particularly focused on ESL instruction in the context of Maldivian Key stage two teachers. Framing the study to include the unique characteristics of the island contexts, a qualitative multiple case study design informed by the interpretivist research paradigm was used in this study. Four schools across Maldives were purposefully selected for this study. Hence, the six teachers who were teaching English for grade six became the participants of this study. Data were collected through in-depth interviews, lesson observations and document reviews. Thematic analysis was used to analyse the descriptive data collected in this study. Furthermore, cross-case and within-case analysis was done to get an in-depth understanding of the similarities and differences between the teachers. The findings of the study suggested that there was a dynamic teacher-tool relationship, which varies from one teacher to another, from one lesson to another and from one activity to another activity. Various factors related to teachers, curriculum tools and the context were identified shaping the teacher-tool relationship. The specific characteristics of the island context including professional guidance available for teachers, the parents’ involvement, short-and long-term job opportunities available in the island, the school goals and the students’ second language experiences played a significant role in shaping the teacher-tool relationship in the remote and isolated islands of the Maldives.